2015
DOI: 10.1088/0953-8984/27/8/085602
|View full text |Cite
|
Sign up to set email alerts
|

Doping-dependent bandwidth renormalization and spin–orbit coupling in (Sr1−xLax)2RhO4

Abstract: We investigate the electronic structure of (Sr1−xLax)2RhO4using a combination of the density functional and dynamical mean-field theories. Unlike the earlier local density approximation plus Hubbard U (LDA+U) studies, we find no sizable enhancement of the spin-orbit splitting due to electronic correlations and show that such an enhancement is a spurious effect of the static mean-field approximation of the LDA+U method. The electron doping suppresses the importance of electronic correlations, which is reflected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…( 1) and ( 2), some discrepancies with the formulae given in Eq. (19) and in [22] can be observed. Contrary to common belief, the Hubbard interactions are smaller in the 4d-TMO than in its 5d-counterpart.…”
Section: Effective Hubbard Interactions From Crpamentioning
confidence: 86%
See 1 more Smart Citation
“…( 1) and ( 2), some discrepancies with the formulae given in Eq. (19) and in [22] can be observed. Contrary to common belief, the Hubbard interactions are smaller in the 4d-TMO than in its 5d-counterpart.…”
Section: Effective Hubbard Interactions From Crpamentioning
confidence: 86%
“…But, as pointed out already earlier [19,20], also in 4d compounds spin-orbit interactions can influence the electronic properties substantially. In Sr 2 RhO 4 , for example, the experimentally observed Fermi surface can only be reconciled with experiments when spin-orbit coupling and electronic Coulomb correlations are taken into account [19][20][21][22]. Here, we give a review of recent efforts to describe correlated spin-orbit physics from first principles, in a combined density functional and dynamical mean-field theory framework [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous ARPES study and first-principles calculation consistently show the presence of zone boundary DLN. [33][34][35] To induce an instability by controlling the rotation angle of RhO 6 octahedra, either by applying electric field or chemical doping would be an intriguing topic for future studies. By means of DFT calculations, it can be shown that the bandwidth of the zone boundary DLN in Sr 2 RhO 4 also changes as a function of the rotational angle.…”
Section: Discussionmentioning
confidence: 99%
“…orbital-selective) behavior, 3) or complex ordering phenomena. [4][5][6][7][8][9] In order to recover the material-specific character of the calculations, DMFT has been combined with DFT 10,11) into the so-called "DFT+DMFT" scheme, which is nowadays one of the most popular workhorses of electronic structure theory for correlated electron materials. Successful applications include transition metals, [12][13][14] transition metal oxides, 4,[15][16][17][18][19][20][21][22][23][24][25][26] lanthanide 27,28) or actinide [29][30][31][32] systems.…”
Section: Introductionmentioning
confidence: 99%